Improving students anecdot writing ability through genius learning strategies and discussion methods - Maria, Vivi; Missriani, Missriani; Fitriani, Yessi (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The purpose of this study was to improve the ability of class X IPS 1 SMA Negeri 4 OKU through genius learning strategies and lecture methods. Research data collection techniques using observation, documentation and tests. The research data analysis technique used a descriptive writing test through direct learning and observation models to see student learning activity. Based on the results of the study, it can be concluded that there is an increase in the ability to write anecdotes through genius learning strategies and lecture methods in class X IPA 1 SMA Negeri 4 OKU. In cycle 1, an average value of 66.68 was obtained, students who achieved completeness were 22 students or the percentage of completeness was 61.11%. In cycle 2 the average value is 69.28%. Students who achieved completeness were 29 students or the average persetanse completeness was 80.56%. Furthermore, in cycle 3 the average value is 76.81. Students who achieved completeness were 34 students or the percentage of student completeness was 94.44%.